Analysis of Student Interest in Cryptocurrency and Traditional Capital Markets: A Case Study at the Faculty of Economics and Business, Universitas Nusantara PGRI Kediri - Setiawan, Rendy (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to analyze the influence of financial literacy, psychological factors, accessibility, and technological innovation on the interest of students of the Faculty of Economics and Business, Universitas Nusantara PGRI Kediri in investing in cryptocurrency and traditional capital markets. Design/Methode/Approach : This study used a quantitative method with a causality approach. Data were collected through a survey using a structured questionnaire designed based on indicators of related variables. The sample was taken using purposive sampling technique from students of the Faculty of Economics and Business, Universitas Nusantara PGRI Kediri. Data analysis was performed using multiple regression to test the effect of independent variables on the dependent variable. Research Finding : The results showed that financial literacy, psychological factors, and accessibility have a positive and significant influence on students' interest in investing. Theoretical contribution/Originality : This study makes a theoretical contribution in understanding the factors that influence students' interest in investing in financial markets. By combining aspects of financial literacy, psychological factors, accessibility, and technological innovation, this study offers a comprehensive perspective that was previously rarely discussed simultaneously in the context of economics students. Practitionel/Policy implication : The findings provide implications for the development of financial literacy programs in higher education, including investment training and more intensive use of financial technology. Educational institutions can utilize technology-based investment applications to improve students' financial skills. The government and financial institutions may also consider regulations that support investment accessibility for the younger generation. Research limitation : This study has limitations in that the sample size is limited to one university, so the results cannot be widely generalized. In addition, the data was collected through a survey that relies on respondents' subjective answers, which may be affected by perception bias. Further studies are recommended to cover a wider population with more varied research methods.